Deep structure of the Vøring Margin: The transition from a continental shield to a young oceanic lithosphere - Fernandez, Manel; Torné, Montserrat; García-Castellanos, Daniel; Vergés, Jaume; Wheeler, J.; Karpuz, Ridvan (Earth and Planetary Science Letters, 2004)
The present-day lithospheric structure across the Norwegian Margin in the Vøring region is presented. The Vøring Margin is characterized by the presence of large volume of magmatic underplating, thick Mesozoic basins, and prominent crustal thinning. Results from recent deep seismic experiments in the Vøring Basin and Vøring Marginal High and 3-D gravity modelling have been implemented in a regional 2-D lithospheric transect that runs from the Norwegian Caledonian Belt to the oceanic domain, crossing the transition between the Precambrian Fennoscandian/Baltic shield and the Cenozoic northern North Atlantic oceanic lithosphere. The modelling approach integrates elevation, gravity, geoid and heat flow data under the assumptions of thermal steady-state and local isostasy. The results confirm and refine the major trends of the crustal geometry which is characterized by a Moho depth varying from about 45 km beneath the Caledonian thrusts, to 30 km beneath the Trøndelag Platform, to 20-14 km beneath the Vøring Basin and to 13 km in the oceanic domain. The lithosphere thins from the Norwegian Caledonian Belt (190 km thick) to the oceanic domain (< 60 km) in a stepwise manner reflecting the progressive seawards migration of lithospheric deformation since the Paleozoic. Our lithospheric thickness results are different from those predicted by post-rift lithospheric cooling models. In the oceanic domain, observed residual bathymetry (∼600 m) is interpreted as the remaining effect of a deep seated thermal perturbation during the upper Cretaceous which would also produce a heat flow anomaly of ∼15 mW m-2. Alternatively, residual bathymetry can be interpreted in the absence of thermal anomalies as produced by depletion of the sublithospheric mantle extending down to 130-230 km depth depending on the density contrast (10-30 kg m-3). © 2004 Elsevier B.V. All rights reserved.